2018
DOI: 10.1017/s1368980018000654
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake in the early years and its relationship to BMI in a bi-ethnic group: the Born in Bradford 1000 study

Abstract: Shortened version of the title: Dietary intake and its relationship to BMIDisclosure statements: This research received no specific grant from any funding agency, commercial or not-for-profit sectors. Acknowledgments:We are grateful to all the families who took part in this study, to the midwives for their help in recruiting them, the paediatricians and health visitors and to the Born in Bradford team which included interviewers, data managers, laboratory staff, clerical workers, research scientists, volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…The self- report questionnaire collected information on participant sociodemographic data, as well as toothbrushing and dietary behaviours, based on validated measures [ 28 , 29 ]. Self-report determinants of toothbrushing were measured against national guidance.…”
Section: Methodsmentioning
confidence: 99%
“…The self- report questionnaire collected information on participant sociodemographic data, as well as toothbrushing and dietary behaviours, based on validated measures [ 28 , 29 ]. Self-report determinants of toothbrushing were measured against national guidance.…”
Section: Methodsmentioning
confidence: 99%
“…49 The same two studies showed a significant reduction in metabolic syndrome with higher fruit intake. 47,48 For measures of cognition, both studies reporting on a cohort of 2868 students identified educational benefits [19][20][21]26,[29][30][31]34,35,42,[62][63][64][65] Blood lipids 19,26,30,31,66 Glycaemia 19,31,34,67,68 Blood pressure 19,31 Puberty 43 Bowel health 44 Vegetables 16 19 487 Body weight 23,24,[26][27][28][29]32,[69][70][71] Blood lipids 26,32 Glycaemia 32 Blood pressure 32,38 Metabolic syndrome [47][48]…”
Section: Other Health Outcomesmentioning
confidence: 99%
“…Body weight [23][24][25][26][27][28][29]32,[69][70][71] Blood lipids 26,32 Glycaemia 32 Blood pressure 25,32,38 Metabolic syndrome 48,49 Bone health 41 Cognition 50,51 Vegetables and fruit 13 5286 Body weight 22,34,35,46,65,72 Blood lipids 33 Glycaemia 34 Blood pressure 36,73,74 Bone health 39,40 Cognition 45 Refined or whole grains 6 10 037 Body weight 26,27 Blood lipids 26,33 Glycaemia 67 Metabolic syndrome 49 Cognition 51 with a higher intake of fruit 50,51 ; however, these benefits were not observed with higher vegetable or wholegrain intakes. 51…”
Section: Fruit 17 22 216mentioning
confidence: 99%
“…dyads compliant with all items of DBOH advice). Dietary data was collected based on child's frequency of consumption, using an established dietary questionnaire used within a similar population 28 . Frequency scoring of food and drinks was nonlinear (e.g.…”
Section: Data Collectionmentioning
confidence: 99%
“…Collecting dietary data presented several challenges. The dietary questionnaire, although a validated data collection method, 28 had limitations: it relied on recall, parents were sometimes unsure of diet at nursery/with grandparents, and it did not account for seasonal differences. Anecdotally, researchers found some parents struggled with de nitions used in the frequency table (e.g.…”
Section: Limitationsmentioning
confidence: 99%